The two lost mountains - Reilly, Matthew (Reilly, Matthew. Jack West Jr. thriller ;, 2020)
"Against all the odds, Jack West Jr found the Three Secret Cities but at a heartbreaking cost. His beloved daughter Lily, it appeared, was slaughtered by Sphinx in a cruel ancient ritual. With his rivals far ahead of him, Jack must now get to one of the five iron mountains - two of which have never been found - and perform a mysterious feat known only as 'The Fall'. Although what is this object on the moon that is connected to it? Amid all this, Jack will discover that a new player has entered the race, a general so feared by the four legendary kingdoms they had him locked away in their deepest dungeon. Only now this general has escaped and he has a horrifying plan of his own ..."--Publisher